DISCURSUS OF WOMEN POLITICAL RIGHTS BASED ON AL-QUR’AN; Empirical study on women’s political participation in Jakarta, Indonesia - Kesuma, Arsyad Sobby; Ali, Syamsuri (Journal of Economic Development, Environment and People, 2019)
The aim of this study is to illustrate the general Islamic view of women and their rights in political participation. Qualitative methods are used with the basis of collecting secondary data sourced from books, journals and scientific publications from relevant agencies. Geographically, the study provides an overview of women’s political participation in Indonesia. This is based on the assumption that the majority of Indonesia’s population are Muslim and the level of women’s political participation in Indonesia is getting better every year. The result of the study is expected to be an overview and the basis of policy development related to increasing women’s political participation in the perspective of Islam